2019
DOI: 10.1161/jaha.119.012330
|View full text |Cite
|
Sign up to set email alerts
|

Oral Bacterial Signatures in Cerebral Thrombi of Patients With Acute Ischemic Stroke Treated With Thrombectomy

Abstract: Background Chronic infections have been reported to be risk factors for both coronary heart disease and ischemic stroke. DNA of oral bacteria, mainly from the viridans streptococci group, has been detected in coronary thrombus aspirates of myocardial infarction and cerebral aneurysms. Viridans streptococci are known to cause infective endocarditis and possess thrombogenic properties. We studied the presence of oral bacterial DNA in thrombus asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 62 publications
3
35
2
3
Order By: Relevance
“…One of the different families between the two groups was Prevotellaceae , which was also decreased in an experimental stroke model and correlated with the extent of brain injury [ 47 ]. The relative abundance of Enterococcus and Streptococcus was also affected by cerebral ischemic stroke [ 48 , 49 ]. Besides, we found that Pasteurella, Peptococcus, and Caproiciproducens were enriched in mice BCCAO ; this was not reported before.…”
Section: Discussionmentioning
confidence: 99%
“…One of the different families between the two groups was Prevotellaceae , which was also decreased in an experimental stroke model and correlated with the extent of brain injury [ 47 ]. The relative abundance of Enterococcus and Streptococcus was also affected by cerebral ischemic stroke [ 48 , 49 ]. Besides, we found that Pasteurella, Peptococcus, and Caproiciproducens were enriched in mice BCCAO ; this was not reported before.…”
Section: Discussionmentioning
confidence: 99%
“…Um importante estudo (Olli et al, 2019) demonstrou um resultado muito importante, onde os pesquisadores encontraram traços de DNA de bactérias orais após analisar amostras de coágulos de 75 pacientes vitimas de AVC. Após remover os coágulos dos pacientes, amostras foram analisadas e foi descoberto que 79% dos coágulos tinham traços de bactérias orais.…”
Section: Discussionunclassified
“…Após remover os coágulos dos pacientes, amostras foram analisadas e foi descoberto que 79% dos coágulos tinham traços de bactérias orais. Ainda segundo esse estudo, existem evidências de que as bactérias orais podem estimular células endoteliais a produzir citocinas pró-inflamatórias e também ativar diretamente as plaquetas sanguínas, chegando a conclusão de que existe uma relação entre bactérias orais e acidente vascular cerebral (Olli et al, 2019).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…It was found that a small amount of LPS significantly affects fibrinogen and the coagulation process, which may indicate the involvement of a very small number of inactive bacteria in inducing inflammation and disease progression. 7 As the studies of Patrakka et al 8 show, streptococci participate in infective endocarditis and have thrombotic properties. An important evidence for bacteria association with these diseases was the detection of deoxyribonucleic acid (DNA) in the coronary thrombosis aspirates of myocardial infarction and cerebral aneurysms.…”
Section: Introductionmentioning
confidence: 98%